Intravenous administration of Penicillin results in therapeutic intravitreal levels in chronic postoperative endophthalmitis - Thabet, Chloe; Gottlieb, Chloe C C; Hurley, Bernard R; Zhang, Guijun; Sherazi, Adeel; Angel, Jonathan B (Université d'Ottawa | University of Ottawa, 2021)
Abstract Importance The role of systemic antibiotics in the treatment of bacterial endophthalmitis remains controversial. While penicillin is a highly effective antibiotic against bacteria that frequently cause endophthalmitis, the ability of systemically administered Penicillin G to penetrate into the vitreous at adequate therapeutic concentrations has not been studied. Its role in the treatment of endophthalmitis, particularly for bacteria for which it is the antibiotic of choice, therefore remains unknown. Objective We sought to determine whether intravenous administration of Penicillin G leads to adequate therapeutic concentrations in the vitreous for the treatment of bacterial endophthalmitis. Design and setting This study was conducted in an ambulatory setting, at the Ottawa Hospital Eye Institute, a university-affiliated tertiary care center, where a 77-year old gentleman with chronic post-cataract surgery Actinomyces neuii endophathalmitis was treated with intravenous Penicillin G (4 × 106 units every 4 h) and intravitreal ampicillin (5000μg/0.1 m1). Main outcomes and measures Intravitreal concentration of Penicillin G and ampicillin were obtained at the time of intraocular lens removal, measured by high-performance liquid chromatography. Results The intravitreal concentration of penicillin and ampicillin was 3.5μg/ml and 0.3μg/ml, respectively. Both the concentration of penicillin and ampicillin were within the level of detection of their respective assays (penicillin 0.06-5μg/ml, ampicillin 0.12–2.5μg/ml). Conclusion and relevance This study shows that intravenous Penicillin G administered every four-hours allows for adequate intravitreal concentrations of penicillin. Future studies are required to determine if the results of this study translate into improved clinical outcomes.